Book review: The State of It: Stories from the Frontline of a Broken Care System. By Chris Wild, Publisher: John Blake Publishing Ltd, ISBN: 1789463904 - Khutso Ranato-Dunbar (Scottish Journal of Residential Child Care)
The State of It is a clarion call from the frontlines of a care system in need of urgent change. The author, Chris Wild, is a care experienced campaigner, advocate and care sector professional. He leverages his own personal story of growing up in care in England from the age of 11 alongside the heart-breaking accounts of many young people he encountered along the way, both as a resident and later a professional in the sector, to call attention to how the system is broken, and suggesting ways in which it can be fixed.